KRITIK FEMINIST PADA PERISTIWA EKSPLOITASI TENAGA KERJA PEREMPUAN DI KOTA SURABAYA - Rena Febrita Sarie; Dwi Lesno Panglipursari; Allen Pranata Putra (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
This study discusses the feminist critique of female labor in the era of neoliberalism in the city of Surabaya. The urgency of this research provides feminism critique as an anti-thesis form of exploitation of female labor in the city of Surabaya. The formulation of this research problem includes: 1) To what extent is the level of exploitation of neoliberal era female workers in the city of Surabaya? 2) What is the role of the government in minimizing the exploitation of women workers? 3) What is the strategy to anticipate the exploitation of female workers? The objectives of this study are 1) Exploring the level of exploitation of female labor; 2) Analyze the government's contribution in minimizing the exploitation of women's labor; 3) Analyze strategies to prevent the exploitation of female workers. Stages of qualitative research methods through empirical studies of in-depth data collection techniques, interviews, focus group discussions, and observations. The results showed that the regulation on the number of working hours should be strictly regulated through the establishment of a special task force used to monitor and evaluate every business actor who is considered to have committed acts of labor exploitation. Keywords: Feminism, Neoliberalism, Labor Exploitation